Influence of season on plasma biochemistry of emu birds - G. Suganya; V. Leela (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The emus are primarily monogamous and seasonal breeders. Blood biochemical parameters and hormones are known to influence production and reproduction in emus. There are no literatures available on the study of blood biochemical parameters during the different periods of breeding seasons. Hence, an attempt was made to evaluate the plasma biochemical profile of adult emu birds during different periods of seasons. The study was conducted in ninety apparently healthy emu birds (forty five of each sex) of 5 to 6 years of age, reared at a commercial emu farm in Tamil Nadu.  Blood samples were collected in heparin coated tubes during the pre-breeding, breeding and post-breeding seasons. Plasma was separated by centrifugation and biochemical parameters such as total protein, albumin, total cholesterol, LDL cholesterol and HDL cholesterol were analyzed using the commercially available kits. The albumin: globulin ratio was then calculated. The experimental data were statistically analyzed by one – way analysis of variance (ANOVA) and post hoc analysis were carried out using Duncan’s test for multiple comparisons using SPSS software version 20 for windows. The results revealed that during the pre-breeding season, the globulin and HDL cholesterol concentrations were significantly higher, whereas, during the breeding season, the total protein, albumin concentration and the albumin: globulin ratio was significantly higher and the total cholesterol and LDL cholesterol concentrations were found to be significantly higher during the post-breeding season. Analysis of plasma biochemistry helps in understanding the reproductive functions of the emu birds.